Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/4505345
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Measuring the Awareness of Chronic Kidney Disease (CKD) with Environmental Evaluation among Adult Diabetic Patients in Hail Region, Saudi Arabia

Abstract: Introduction. Chronic kidney disease (CKD) is one of the main chronic complications of T2DM that happens among T2DM patients who have uncontrolled glucose. Because CKD is considered a silent disease, the diagnosis is usually made at late stages when there will be few chances to prevent the adverse outcome. Aim. The goal of this study was to assess adult diabetic patients’ awareness of developing chronic kidney disease at the community level in Hail region, Saudi Arabia, in 2022. Patients and Methods. This is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…A study conducted in Saudi Arabia by Nahlah Fahad et al showed that the level of knowledge about CKD among diabetic patients was poor, moderate, and good among 46.8%, 29.2%, and 24%, respectively [31].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Saudi Arabia by Nahlah Fahad et al showed that the level of knowledge about CKD among diabetic patients was poor, moderate, and good among 46.8%, 29.2%, and 24%, respectively [31].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%